Use of GABAergic sedatives after subarachnoid hemorrhage is associated with worse outcome—preliminary findings - Hertle, Daniel; Beynon, Christopher; Neumann, Jan-Oliver; Santos, Edgar; Sánchez-Porras, Renán; Unterberg, Andreas; Sakowitz, Oliver (Journal of clinical anesthesia, 2016)
Recent experimental evidence identified GABAergic sedation as a possible cause for deprived neuroregeneration and poor outcome after acute brain injury. Patients with aneurysmal subarachnoid hemorrhage are often sedated, and GABAergic sedation, such as midazolam and propofol, is commonly used. Retrospective cohort study based on a prospectively established database. Single-center neurointensive care unit. Twenty-nine patients after subarachnoid hemorrhage. Noninterventional study. The relationship between mean GABAergic sedative dose during the acute phase and outcome after 6 months according to the Glasgow Outcome Scale, and initial Glasgow Coma Scale was investigated. Use of GABAergic sedatives was negatively correlated with Glasgow Outcome Scale (r2=0.267; P=.008). Administration of sedatives was independent of the initial Glasgow Coma Scale. GABAergic sedatives flunitrazepam, midazolam, and propofol were used differently during the first 10 days after ictus. Administration of GABAergic sedation was associated with an unfavorable outcome after 6 months. To avoid bias (mainly through the indication to use sedation), additional experimental and comparative clinical investigation of, for example, non-GABAergic sedation, and clinical protocols of no sedation is necessary.